Breathe out and learn: Expiration‐contingent stimulus presentation facilitates associative learning in trace eyeblink conditioning. (26th April 2019) - Waselius, Tomi; Wikgren, Jan; Penttonen, Markku; Nokia, Miriam S.
Abstract: Rhythmic variation in heart rate and respiratory pattern are coupled in a way that optimizes the level of oxygen in the blood stream of the lungs and the body as well as saves energy in pulmonary gas exchange. It has been suggested that the cardiac cycle and respiratory pattern are coupled to neural oscillations of the brain. Yet, studies on how this rhythmic coupling is related to behavior are scarce. There is some evidence that, for example, the phase of respiration affects memory retrieval and the electrophysiological oscillatory state of the limbic system. It is also known that the phase of the cardiac cycle and hippocampal electrophysiological oscillations alone affect learning. Here, we studied whether the timing of training trials to different phases of respiration affects learning trace eyeblink conditioning in healthy adult humans. Trials consisting of a neutral conditioned stimulus (200‐ms tone) and a slightly aversive unconditioned stimulus (100‐ms air puff toward the eye), presented with a 600‐ms trace interval, were timed to either inspiration or expiration. A control group was trained regardless of respiratory phase. We found that, at the end of training, the rate of conditioned responses was higher in the group trained at expiration than it was in the other two groups. That is, brain state seems to fluctuate as a function of respiratory rhythm, and this fluctuation is also behaviorally relevant, exerting its effect on, at the least, a simple form of associative learning. Abstract : It has been hypothesized that the brain and the body have various entrained rhythms. For example, phases of respiration are time‐locked to slow electrophysiological oscillations in the limbic system. Even further, in mice, sharp wave‐ripples occur more likely in the expiration phase of the respiration pattern. To study the effect of the respiration rhythm on learning, we subjected humans to trace eyeblink conditioning. As a result, learning was enhanced when the conditioned stimulus and unconditioned stimulus were both presented during expiration. This finding should be of interest to a wide population of scientists.